Game-based e-learning for urban tourism education through an online scenario game. Issue 4 (1st October 2020) - Chan, Chung-Shing; Chan, Yat-hang; Fong, Tsz Heung Agnes
Abstract: This paper introduces an e-Learning for urban tourism education through a scenario-based game of a hypothetical city. This scenario game set a good example to integrate components of e-Learning, gamification and scenario-based platform in tourism geography and planning education. This study evaluated the effectiveness of urban tourism scenario game in terms of knowledge enrichment, attitudinal change and platform usability reported by a sample of voluntary university students (n = 30). The overall effectiveness of the game is found generally positive. Paired-sampled t-test results show that this game platform is successful in improving participants' fundamental knowledge about new concepts, models and issues in the urban tourism context. The nature of tourism study in social science involves dynamism of perception and views, and thus leading to attitudinal changes of the game players although these changes are only statistically significant in one-fourth of the attitudinal attributes. The usability is the shortcomings of the game since this dimension is difficult to control except some technical elements. From the statistical results, the game does not reach a high expectation of usability except the educational design of the game. Some discussions and suggestions are made to enhance the effectiveness of game-based learning in tourism education through clever integration of modes of learning and other e-Learning elements.